KEJANG PADA PASIEN MENINGITIS BAKTERI DEWASA - Putu Setiani; Rindha Dwi Sihanto; I Gusti Ngurah Angga Nugraha (Bajang Institute, 2026)
Background: Seizures are common neurological complications of Bacterial Meningitis in Adults (BMA) and significantly related with poor clinical outcome, but reported data epidemiology and characteristics of seizures had been limited. Objective: To evaluate the occurrences and outcome in BMA patient with seizures. Methods: Cross-sectional descriptive analytic study taken in 120 hospitalized BMA patients at Sanglah General Hospital Denpasar from January 2012 to December 2017. Data collection based on the patient's medical record data. Data processing using SPSS 20.0. Results: Seizures occurred in 20 of 120 patients (16,7%) with mean 38 years old (SD ±16,1) and male predominace in 13 patients (65%). Seizure type were generalized tonic clonic 60%, secondary generalized partial 35%, and generalized tonic 5%. Pre-hospital seizures in 3 patients (15%) and in-hospital seizures 17 patients (85%), with the median of onset seizures 46,50 hours (range 4-168 hours). Head CT scan and MRI abnormal in 95 patients. EEG normal in 12 patients (60%), others not performed in 8 unstabilized patients (40%). Antiepileptic drugs phenytoin in 16 patients (80%) and carbamazepine in 4 patients (20%). Death occurred in 35% seizures (p= 0,021), 100% generalized tonic type (p= 0,021), 45,4% early onset in-hospital (p= 0,013), and 100% status epilepticus (p= 0,036). Conclusion: Seizures in BMA patients occurred frequently in productive male, generalized tonic clonic type, with normal EEG. Death as poor outcome related to generalized tonic clonic type, early onset < 48 hours in-hospital seizuress, and status epilepticus.